2017
DOI: 10.3389/fpsyg.2017.00592
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Processing of Emotional Words in the Absence of Awareness: The Critical Role of P2

Abstract: It has been long debated to what extent emotional words can be processed in the absence of awareness. Behavioral studies have shown that the meaning of emotional words can be accessed even without any awareness. However, functional magnetic resonance imaging studies have revealed that emotional words that are unconsciously presented do not activate the brain regions involved in semantic or emotional processing. To clarify this point, we used continuous flash suppression (CFS) and event-related potential (ERP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Many studies have examined the differences in the processing of different words on a behavioral level, but not sufficient for pain words for persons with pain. Our findings supported those of previous studies by reporting facilitative processing of special words [ 7 , 22 , 25 ] and added new evidence for a particular group of people.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many studies have examined the differences in the processing of different words on a behavioral level, but not sufficient for pain words for persons with pain. Our findings supported those of previous studies by reporting facilitative processing of special words [ 7 , 22 , 25 ] and added new evidence for a particular group of people.…”
Section: Discussionsupporting
confidence: 91%
“…After examining the grand-averaged waveforms in our study and referring to those in previous studies [ 7 , 22 ], we set the time windows for the ERP components as follows: N1, 70-170 ms, with a peak at about 120 ms; P2, 150-250 ms, with a peak at about 200 ms; and N3, 250-350 ms, with a peak at about 300 ms. We included nine electrodes in the analysis on the basis of previous findings according to the frontal (F3, Fz, and F4), central (C3, Cz, and C4), and partial (P3, Pz, and P4) sides, as reported elsewhere [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Campbell and Kenny (1999, pp. xiii) Examinations of the capacities and capabilities of nonconscious processes have been part of experimental psychology from the late 19th century (e.g., Peirce & Jastrow, 1885;Sidis, 1898) throughout the 20th century (e.g., Bruner, 1957;Dehaene et al, 1998;Greenwald, 1992;Greenwald et al, 1996;Marcel, 1983) and are still flourishing in the second decade of the 21st century (e.g., Abir et al, 2017;Faivre et al, 2014;Lei et al, 2017;Moors et al, 2017;Salomon et al, 2017). In recent decades, the modal view suggests that nonconscious mental processes are an inherent part of human psychology (e.g., Bargh et al, 2012;Breitmeyer & Ögmen, 2006;Capa et al, 2011;Dehaene et al, 2006;Dijksterhuis et al, 2006;Faivre et al, 2014;Goldstein & Hassin, 2017;Hassin, 2013;Hassin & Sklar, 2014;Lamy et al, 2008;Sklar et al, 2018;Van Opstal et al, 2010;Zacks et al, 2007).…”
mentioning
confidence: 99%
“…For example, using an emotional Stroop task in which subjects completed color-relevant tasks and word-relevant tasks, in the color-relevant tasks the color of word was identified and in the word-relevant tasks the words were classified as threatening or not, earlier research found that threat words were associated with a larger P2 amplitude across tasks ( Thomas et al, 2007 ). Therefore, Lei et al (2017) showed that P2 play an important role in the unconscious processing of emotional words.…”
Section: Introductionmentioning
confidence: 99%